Gangguan Fonologis Disartria Aktris Junior Roberts dalam Wawancara Media Hiburan - Amanda, Dea; Khairunissa, Tsabitah Zoya; Nurjam’an, Ichsan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the phonological disorder in the form of mild articulatory dysarthria experienced by actress Junior Roberts in an entertainment media interview on the Cinema 21 YouTube channel. The study was conducted using a phonological approach, specifically articulatory phonetics, to analyze the inaccuracy of pronunciation of language sounds in spontaneous speech. This study used a qualitative descriptive method with the Free Listening and Speaking (SBLC) technique as a means of data collection. The analysis results indicate that the phonological disorder experienced by the subject is evident in the phoneme /r/ through three main processes: substitution (/r/ is replaced by /l/ or /y/), elision (the /r/ sound is lost), and distortion (the /r/ sound is heard muffled). This disorder is caused by articulatory muscle weakness due to neuromotor dysfunction. Despite this, the subject displayed a positive attitude and made her speech characteristics a personal identity in the entertainment world. This study confirms that the study of phonology does not only focus on the sound aspects of language but also encompasses the physiological, psychological, and social dimensions that influence human speech production.